2018
DOI: 10.2196/mental.9950
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Use and Opinions About New eHealth Technologies Among Patients With Psychosis: Structured Questionnaire

Abstract: BackgroundDespite a growing interest in the use of technology in order to support the treatment of psychotic disorders, limited knowledge exists about the viability and acceptability of these eHealth interventions in relation to the clinical characteristics of patients.ObjectiveThe objective of this study was to assess the access and use of, as well as experiences and interest in, new technologies using a survey of patients diagnosed with early psychosis compared with a survey of patients diagnosed with chroni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 33 publications
4
38
0
Order By: Relevance
“…With regard to the feasibility of the app, no significant differences were found between the ReMindCare group and the TAU group in terms of sociodemographic characteristics except for native country. The feasibility of this intervention aligns with the results obtained in our previous study [ 8 ], where we found no differences in terms of sociodemographic characteristics and interest in using eHealth interventions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…With regard to the feasibility of the app, no significant differences were found between the ReMindCare group and the TAU group in terms of sociodemographic characteristics except for native country. The feasibility of this intervention aligns with the results obtained in our previous study [ 8 ], where we found no differences in terms of sociodemographic characteristics and interest in using eHealth interventions.…”
Section: Discussionsupporting
confidence: 89%
“…Smartphone apps have been proposed as tools to mitigate social isolation, lack of access to care, and other triggers caused by the pandemic [ 3 - 5 ]. Researchers have already demonstrated that access to and use of technology among people with psychosis is nearly equivalent to that in the general population [ 6 - 8 ], but less is known about the actual efficacy of apps in care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A common strategy some individuals with severe mental health problems use to self‐manage is to use digital devices/tools/systems/platforms to access information about mental health problems on the Internet. Recent surveys have reported rates of mental health online information‐seeking by people with severe mental health problems of between 38% and 78% (Bauer et al ., ; Bonet et al ., ; Gay, Torous, Joseph, Pandya, & Duckworth, ). Additionally, qualitative studies reveal that many people interviewed with psychosis describe searching for information about mental health online to aid their own understanding of their experiences; to read information about medication, side effects, and diagnosis; and to seek information about coping skills (Aref‐Adib et al ., ; Lal, Nguyen, & Theriault, ).…”
Section: How Are People Currently Using Technology To Support Their Wmentioning
confidence: 99%
“…[8,[27][28][29][30]). Furthermore, recent survey-based studies have reported that many people with severe mental health problems are amenable to receiving technology-delivered support [31][32][33] and already use technology to facilitate self-management and assessment through activities such as information-seeking, symptom monitoring, medication and appointment reminders and receiving support from others online [31,34,35]. However, evidence regarding service user views towards DHIs and ideas for future developments is limited and survey-based designs have not gathered in-depth and detailed information that can be yielded qualitatively [36].…”
Section: Introductionmentioning
confidence: 99%